The prognostic role of controlling nutritional status and skeletal muscle mass in patients with hepatocellular carcinoma after curative treatment. Issue 12 (17th October 2022) - Tamai, Yasuyuki; Iwasa, Motoh; Eguchi, Akiko; Shigefuku, Ryuta; Sugimoto, Ryosuke; Tanaka, Hideaki; Kobayashi, Yoshinao; Mizuno, Shugo; Nakagawa, Hayato
Abstract : Background: Nutritional status and skeletal muscle mass affect the prognosis of hepatocellular carcinoma (HCC). Nutritional status is closely associated with skeletal muscle mass. Here, we investigate the effect of controlling preoperative nutritional status and skeletal muscle mass on the prognosis of HCC after curative treatment. Methods: This retrospective analysis contained 181 patients who received curative treatment of HCC including liver resection or radiofrequency ablation (RFA) therapy. Nutritional status and skeletal muscle mass were evaluated prior to therapy using the controlling nutritional status (CONUT) score and psoas muscle mass index (PMI), respectively. Associations of predictor variables with overall survival (OS) and progression-free survival (PFS) were determined using Cox proportional hazards regression and CHAID decision tree algorithm analysis. Results: A total of 111 patients (61.3%) were determined to be of poor nutritional status and 100 patients (55.2%) had muscle mass depletion. Patients with PS 0, Barcelona clinic liver cancer (BCLC) stage 0, low CONUT score, and high PMI showed significantly better OS than those with PS 1, BCLC stage A, high CONUT score, and low PMI. Multivariate analysis indicated that a high CONUT score [hazard ratio (HR) 4.130; 95% confidence interval (CI), 1.713–9.958; P  < 0.01) and low PMI (HR 4.625; 95% CI, 1.704–12.549; P  < 0.01) found to be useful for predicting OS in patients after curative treatment of HCC. Regarding PFS, a significant predictor was only tumor numbers in univariate analysis (HR 2.147; 95% CI, 1.350–3.414; P  = 0.001). In decision tree analysis, the mortality rate was 28.8%, 12.5%, and 1.9% in patients with a high CONUT score, with a low CONUT score-low PMI, or with a low CONUT score-high PMI, respectively. Conclusion: The combined CONUT score and PMI were found to be independent predictors of OS in HCC patients after liver resection or RFA.